Theoretical basis and practical aspects of small specimen creep testing - Hyde, Thomas H.; Hyde, Christopher J.; Sun, Wei (SAGE, 2013)
Interest in and the application of small specimen creep test techniques are increasing. This is because it is only possible to obtain small samples of material in some situations, for example, the scoop samples that are removed from in-service components, the heat-affected zones that are created when welds are used to join components and the desire to produce only small amounts of material in alloy development programmes. It is therefore important to review and compare the theoretical basis and practical aspects of each of the small specimen creep testing methods, in order to clearly understand which of the methods is the best for any specific application. This article provides the theoretical basis for each commonly used test method.